Fragment Growing to Design Optimized Inhibitors for Human Blood Group B Galactosyltransferase (GTB). (8th July 2019) - Strecker, Claas; Peters, Hannelore; Hackl, Thomas; Peters, Thomas; Meyer, Bernd
Abstract: Human blood group B galactosyltransferase (GTB) catalyzes the galactosylation of the H antigen and is responsible for the formation of the blood group antigen of phenotype B. The ABO blood group system is well studied and routinely serotyped before transfusion and transplantation. Blood type subgroups have been repeatedly linked to an increased occurrence of diseases (e.g., a highly increased incidence rate for pancreatic cancer for individuals with blood group phenotype B). 3‐Phenyl‐5‐(piperazin‐1‐yl)‐1, 2, 4‐thiadiazole 1 has previously been described to inhibit GTB with a K i value of 800 μm . In this work, we describe a computer‐guided fragment‐growing approach for the optimization of this fragment that was subsequently realized by synthesizing the most promising ligands. Enlarging the phenyl moiety of fragment 1 to a naphthyl moiety resulted in ligand 3‐(naphthalene‐1‐yl)‐5‐(piperazin‐1‐yl)‐1, 2, 4‐thiadiazole 2 a, which shows a threefold improvement in binding affinity ( K i =271 μm ). Abstract : To B or not to B? Human blood group B galactosyltransferase (GTB) is responsible for the formation of the blood group antigen of phenotype B. Individuals of non‐O phenotypes have an increased incidence rate for various cancer types. In this work, a fragment‐growing approach is described that resulted in ligand 2 a (shown), which inhibits GTB with a K i value of 271 μm .